Capital budgeting practices in Spain - Pablo de Alonso; Gabriel de Fuente; Pablo San Martin (BRQ Business Research Quarterly, 2015)
This paper seeks to shed further light on the capital budgeting techniques used by Spanish companies. Our paper posits that the gap between theory and practice might be related to the nature of sources of value and to the efficiency of mechanisms aligning managerial and shareholder incentives, rather than to resource restrictions or model misinterpretation. We analyze data from a survey conducted in 2011, the final sample comprising 140 non-financial Spanish firms. Our findings show a behaviour pattern similar to that reported in prior research for firms in other countries. Particularly noteworthy is that payback appears to be the most widely used tool, while real options are used relatively little. Our results confirm that size and industry are related to the frequency of use of certain capital budgeting techniques. Further, we find that the relevance of growth opportunities and flexibility is an important factor explaining the use of real options."
Keywords: 650; Corporate investment; NPV; IRR; Payback; Real options; Survey